2017
DOI: 10.1002/ange.201707037
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable Tin Perovskites Co‐crystallized with Three Halides for Carbon‐Based Mesoscopic Lead‐Free Perovskite Solar Cells

Abstract: We synthesized and characterized methylammonium (MA) mixed tri-halide tin perovskites (MASnIBr 2Àx Cl x ) for carbon-based mesoscopic solar cells free of lead and holetransporting layers.V aried SnCl 2 /SnBr 2 ratios yielded tin perovskites with three halides (I, Br,a nd Cl) co-crystallized inside the tin-perovskite.W hen the SnCl 2 proportion was ! 50 %( x ! 1), phase separation occurred to give MAS-nI 3Ày Br y and MASnCl 3Àz Br z in the stoichiometric proportions of their precursors,c onfirmed by XRD.Ad evic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…The effect of mixing halides on the phase stability was investigated Diau team. 200 The results showed that 48 large radius difference between Cland Iinduced incomplete solid solutions in MASnI 3-x Cl x , which could be mediated by incorporation of middle-sized Brto form stable tri-halide Sn-PVSKs. Interfacial Band Alignment: The afore-mentioned strategies focused on preparing ambient stable and high-quality Sn-PVSK.…”
Section: Atmospheric Degradationmentioning
confidence: 93%
See 1 more Smart Citation
“…The effect of mixing halides on the phase stability was investigated Diau team. 200 The results showed that 48 large radius difference between Cland Iinduced incomplete solid solutions in MASnI 3-x Cl x , which could be mediated by incorporation of middle-sized Brto form stable tri-halide Sn-PVSKs. Interfacial Band Alignment: The afore-mentioned strategies focused on preparing ambient stable and high-quality Sn-PVSK.…”
Section: Atmospheric Degradationmentioning
confidence: 93%
“…For instance, it was reported the E g of MASnX 3 can be tailored over a large range of the visible spectrum with different Br -/Cl -/Iratio. 200 Figure 13D and E show the energy diagrams and absorption spectra of MA based Sn-PVSKs depending on various halide combinations. Similar phenomenon was also observed Brdoped CsSnI 3 .…”
Section: Atmospheric Degradationmentioning
confidence: 99%
“…Tin double halides, such as SnF 2 and SnCl 2 , were first developed as antioxidant agents and tin (II) source compensators to stabilize the Sn 2+ , as shown in Figure . [ 35,39,40 ] After that, a series of reducing additives including the hypophosphorous acid (HPA), metallic Sn powder, and formic acid were exploited to purify the Sn 4+ impurity in precursor solution to reduce the Sn vacancies and pinholes in tin perovskite film, which increases the film coverage and thus leads to a better morphology. [ 41–44 ] Moreover, large‐size organic ammoniums and Lewis base molecules were used to optimize the crystallization process to further improve the efficiency and stability of tin PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15,21 ] To suppress the instability of Sn 2+ , antioxidant additives such as SnF 2 , SnCl 2 , pyrazine, and hydroxybenzene sulfonic acid have been reported as sacrificial agents to prevent the oxidation and improve the carrier lifetime in tin perovskite films. [ 22–25 ] Recently, a liquid formic acid was exploited as a volatile reducing solvent for the film deposition to eliminate the Sn 4+ impurities in SnI 2 precursor. [ 26 ] Unsuitable interface band alignment is another factor that induces the voltage loss in TPSCs.…”
Section: Introductionmentioning
confidence: 99%